Bacteria-instructed synthesis of polymers for self-selective microbial binding and labelling - Magennis, Eugene Peter; Fernandez-Trillo, Francisco; Sui, Cheng; Spain, Sebastian G.; Bradshaw, David; Churchley, David; Mantovani, Giuseppe; Winzer, Klaus; Alexander, Cameron (Nature Publishing Group, 2014)
The detection and inactivation of pathogenic strains of bacteria continues to be an important therapeutic goal. Hence, there is a need for materials that can bind selectively to specific microorganisms, for diagnostic or anti-infective applications, but which can be formed from simple and inexpensive building blocks. Here, we exploit bacterial redox systems to induce a copper-mediated radical polymerisation of synthetic monomers at cell surfaces, generating polymers in situ that bind strongly to the microorganisms which produced them. This ‘bacteria-instructed synthesis’ can be carried out with a variety of microbial strains, and we show that the polymers produced are self-selective binding agents for the ‘instructing’ cell types. We further expand on the bacterial redox chemistries to ‘click’ fluorescent reporters onto polymers directly at the surfaces of a range of clinical isolate strains, allowing rapid, facile and simultaneous binding and visualisation of pathogens.